THE PHENOMENON OF TEACHERS IN APPLYING THE PROBLEM-BASED LEARNING MODEL TO STUDENTS AT MI MIFTAHUL ULUM - Rohalia, Zakia; Soliha, Imro Atus; Yulina Fadilah (Al-Mubin, 2025)
ABSTRACT This study examines the meaning and application of Problem Based Learning (PBL) by teachers at Madrasah Ibtidaiyah Miftahul Ulum, Probolinggo Regency, as an effort to integrate Islamic values into the learning process. With a descriptive qualitative method, data was collected through semi-structured interviews, direct observations, as well as analysis of the Learning Implementation Plan (RPP) and teacher evaluation notes. The findings show that teachers use PBL as a contextual space to instill the principles of ta'awun, tawakkal, honesty, and responsibility in each stage of problem-solving that is close to the student's experience. Reflective approaches and dialogical discussions accompanied by the integration of Qur'anic verses and hadith have been proven to improve students' critical thinking skills while strengthening their spiritual awareness. The main obstacles identified are limited technological facilities and infrastructure, high administrative burden, and lack of special training for teachers. This study also highlights the active role of students in designing solutions and the influence of PBL on their learning motivation. Therefore, it is recommended to provide continuous intensive training for educators, adjust curriculum policies more flexibly, improve supporting facilities, and establish a community of practice between teachers. This step is expected to support the consistency of PBL implementation, improve the quality of learning outcomes, and form students' religious character holistically. The results of the research are expected to support the development of a more contextual madrasah curriculum